Redesign of Material Storage Warehouse Layout Using Shared Storage Method (Case Study: Chemical Warehouse) - Desnita.S, Yolanda Lisa; Nugroho, Adi (Greeners: Journal of Green Engineering for Sustainability, 2025)
The research was conducted in a material storage warehouse where some items were placed outside the warehouse due to space limitations. Storing items outside the warehouse can lead to a decline in product quality and financial losses. Therefore, this study aims to redesign the warehouse layout using Shared Storage method to optimize storage capacity. By analyzing storage needs and capacity, this research seeks to develop a new layout to enhance warehouse storage capacity. This study employs a quantitative approach, collecting data on material demand frequency, the existing warehouse layout, and the number of materials. Calculations were performed to determine the required aisle width and the total storage area needed for each type of material, considering forklift usage and pallet dimensions. The research findings indicate that the proposed warehouse layout increases storage capacity from 810 pallets to 1,298 pallets, representing a 60.25% increase. This improvement not only addresses space constraints but also contributes to better product management. The study provides practical implications for warehouse managers looking to implement space-saving strategies and improve operational efficiency. The Shared Storage method has proven to be a viable solution for warehouses facing similar challenges in maximizing storage space.